(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2016)
While looking for a topic to write on our ‘Art Education’, a chance encounter with a young artist holding a ‘Bachelor’s Degree in Fine Arts’ offered an important eye-opener often ignored by all – the quality of ‘the qualified artists’ we produce. It’s true the said artist proved to be an unpleasant example but he reminded us all – mentors, planners, educationists and all the stakeholders all alike that we have failed. Then and there, I concluded we need to make immediate soul-searching ‘where did we go wrong and what proved us inept in our delivery.’